Implementasi Suku Bunga Pinjaman terhadap Produk Gadai Kredit Cepat Aman (KCA) PT Pegadaian Cabang Daya Kota Makassar - Indriyani Al-qadri Maharani S. Ibrahim; Aryanti Inayah; Nur Syamsuriana (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The implementation of loan interest rates plays a crucial role in the Fast Secure Credit (Kredit Cepat Aman/KCA) pawn product offered by PT Pegadaian Daya Branch, Makassar City. A qualitative approach was employed using observation, in-depth interviews, and documentation to examine how interest rates are applied and how they affect customers and company revenue. Research informants consisted of internal Pegadaian staff directly involved in credit assessment and loan disbursement processes. The findings indicate that interest rates for KCA products are determined based on policies issued by the head office, taking into account the appraised value of collateral and loan classification. As a result, KCA offers relatively lower interest rates compared to other pawn products. Transparent interest calculations, a loan period of up to 120 days, and fast and simple procedures have increased public interest in utilizing this product. Furthermore, the implementation of loan interest rates in KCA has contributed positively to the growth of PT Pegadaian Daya Branch’s revenue over recent years. These findings highlight that competitive interest rate policies combined with efficient credit management can enhance customer trust while supporting the company’s financial performance.